Advice Methods in Children's Education in Q.S. Luqman verse 13 - M. Arifin Ilham; Rosdialena (Konsultan Jurnal Ilmiah Indonesia, 2026)
This article examines the method of advice (Mauizhah) in child education as contained in QS Luqman verse 13. Luqman al-Hakim’s advice to his son, which begins with the prohibition of shirk (associating partners with Allah), serves as a foundational model of Islamic parenting rooted in tawhid. Using a qualitative approach with library research design, this study analyzes Quranic interpretations and relevant academic literature published from 2020 to 2024. The findings reveal that the method of advice in QS Luqman verse 13 is characterized by three key elements: it is delivered with love and compassion using the expression “ya bunayya” (O my dear son), it prioritizes the foundation of monotheism as the primary substance of education, and it employs a gentle yet firm approach suited to a child’s developmental stage. This study affirms that the advisory method of Luqman remains highly relevant as a model for contemporary Islamic education, especially in forming children’s aqidah and moral character within the family environment.